2020
DOI: 10.1212/nxi.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity in pregnancy and postpartum in women with MS who suspended rituximab and natalizumab

Abstract: ObjectiveTo evaluate risks of disease reactivity during pregnancy and postpartum following rituximab (RTX) and natalizumab (NTZ) suspension in women with MS.MethodsAn observational cohort study of all women with MS disease onset before childbirth between 2006 and 2017. Women were identified through the Swedish MS Registry, a nationwide clinical register, with substratification into 3 groups: women who suspended RTX and NTZ within 6 months before conception and women who were not treated with any disease-modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…While presenting a high efficacy, NTZ’s protection against disease reactivation starts to decline from the eighth week after the last infusion due to its pharmacokinetics 5. Women who interrupt NTZ for maternity planning encounter an increased risk of relapses before or during pregnancy due to the rapid immune reconstitution after treatment interruption,6–9 which is unmitigated by pregnancy-induced immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…While presenting a high efficacy, NTZ’s protection against disease reactivation starts to decline from the eighth week after the last infusion due to its pharmacokinetics 5. Women who interrupt NTZ for maternity planning encounter an increased risk of relapses before or during pregnancy due to the rapid immune reconstitution after treatment interruption,6–9 which is unmitigated by pregnancy-induced immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Disease reactivation following NAT cessation prior to or during pregnancy is well recognized and can lead to the accumulation of permanent disability ( 6 , 39 41 ). Even the postpartum period entails an increased relapse risk and could be linked to a high level of inflammatory radiographic disease activity as it was shown in a recent study ( 3 , 4 , 11 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…196,197 It has been extensively reported that discontinuing natalizumab before conception can result in a high risk of relapse during pregnancy and postpartum, radiological activity, and disability progression. 90,91,157,171,185,[198][199][200] Stopping natalizumab prior to pregnancy is associated with rebound relapses and up to 37% of women who stopped it prior to pregnancy reportedly suffered relapses during pregnancy. 157 A longer washout period seems to be associated with a greater risk of relapse during pregnancy 91,171,201 and disability progression.…”
Section: Patients Receiving Dmtsmentioning
confidence: 99%
“…In an observational retrospective cohort study, discontinuing rituximab before pregnancy was found to result in a significantly better control of disease activity during pregnancy and postpartum versus stopping natalizumab. 199 …”
Section: Management Of Ms During the Pre-pregnancy Period ( Box 1 )mentioning
confidence: 99%